Horizons of Difference : Rethinking Space, Place, and Identity with Irigaray. - Crapo Kim, Ruthanne; Russell, Yvette; Sharp, Brenda (State University of New York Press, 2022)
Edited collection engaging Luce Irigaray's work and pushing it in important new directions.
Keywords: Irigaray, Luce; Gender identity -- Philosophy.; Identité de genre -- Philosophie.; Gender identity -- Philosophy